Complications in Transanal Total Mesorectal Excision (TATME) – Early Experience - Martin Karamanliev; Tsanko Yotsov; Dobromir Dimitrov (Journal of Biomedical & Clinical Research, 2022)
Transanal total mesorectal excision (TaTME) is a trending and promising surgical procedure to treat rectal cancer with oncologically oriented precision. Complication rates are promising after the learning curve is passed. A prospective study on the first 12 consecutive TaTME patients was done. The primary aim was the intraoperative and the early and late postoperative complications rate. Оne persisting failure as an intraoperative complication was reported: two anastomotic leaks and a ventral hernia as postoperative complications. TaTME is safe in terms of intra- and postoperative complications.